Prevalence and predictors of false positive QTc prolongation by the automated measurement - Alqarawi, Wael; Allwaim, Marwah (Frontiers in Cardiovascular Medicine, 2024)
Background Corrected QT (QTc) is an important electrocardiographic (ECG) interval. Physicians rely on automated QTc provided by ECG machines while the manual method is the recommended method. We sought to assess the prevalence and predictors of false positive QTc prolongation by the automated measurement. Methods and results Consecutive ECGs were retrieved from the ECG database at King Khaled University Hospital. Manual QT was measured by a trained physician using the tangent method and was corrected for heart rate and QRS duration. Automated QTc measurement was recorded by the ECG machine. “Long QT (LQT)” was defined as QTc≥470 ms for males and ≥480 for females. False positive LQT was defined as LQT by automated QTc but not manual QTc. Pre-determined factors were included in a multivariate logistic regression to assess predictors of false positive LQT. A total of 567 ECGs were included in this study. Automated QTc was longer than manual QTc (440 ms [±35] vs. 417 ms [±35], respectively) which resulted in a high negative predictive value (NPV) (99%) and a low positive predictive value (PPV) (32%). Male gender and abnormal rhythm were found to be independently associated with false positive LQT (OR = 1.9 [95% 1.1–3.5], p = 0.03 and OR = 3.1 [95% 1.2–8.3], p = 0.02; respectively). Conclusion Automated QTc measurement is unreliable for detecting long QT, necessitating manual verification and further research to enhance its accuracy.